ONE-DAY INPATIENT TRENDS IN NON VALVULAR ATRIAL FIBRILLATION - Amado, Carolina (2022)
Non valvular atrial fibrillation (NVAF) is the most common sustained arrhythmia in adults associated with aging, male sex, hypertensive and coronary cardiovascular disease and diabetes.The authors performed a retrospective study which pretended to evaluate inpatients of an internal medicine department with the diagnosis of NVAF, in one random chosen day. From 68 patients, 36% (n=26) had previous diagnosis of NVFA. These patients were older, more frequently woman and with moderate to severe thromboembolic risk. They also had high prevalence of arterial hypertension and diabetes. Most of the patients were under hypocoagulation with LWMH and heart rate control.Due to high relative prevalence of inpatient NVFA, doctors should be aware of the risk-benefit of hypocoagulation and hear rate vs rhythm control.